2013
DOI: 10.1016/j.yjmcc.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Myofilament Ca2+ desensitization mediates positive lusitropic effect of neuronal nitric oxide synthase in left ventricular myocytes from murine hypertensive heart

Abstract: Neuronal nitric oxide synthase (NOS1 or nNOS) exerts negative inotropic and positive lusitropic effects through Ca(2+) handling processes in cardiac myocytes from healthy hearts. However, underlying mechanisms of NOS1 in diseased hearts remain unclear. The present study aims to investigate this question in angiotensin II (Ang II)-induced hypertensive rat hearts (HP). Our results showed that the systolic function of left ventricle (LV) was reduced and diastolic function was unaltered (echocardiographic assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 31 publications
5
39
1
Order By: Relevance
“…1 Although cardiac metabolism and -oxidation may have downregulated in hypertrophy and in heart failure myocardium, it may not be the case in the model of the current study. Our previous reports clearly presented in echocardiography assessment that myocardial contraction was not altered despite pressure-overload in these rats [13]. F-FTHA uptake in both groups.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…1 Although cardiac metabolism and -oxidation may have downregulated in hypertrophy and in heart failure myocardium, it may not be the case in the model of the current study. Our previous reports clearly presented in echocardiography assessment that myocardial contraction was not altered despite pressure-overload in these rats [13]. F-FTHA uptake in both groups.…”
Section: Discussionsupporting
confidence: 56%
“…In the myocytes from healthy heart, nNOS-derived NO attenuates basal contractility of cardiac myocytes by modulating the activities of L-type Ca 2+ channels (LTCC) in the plasma membrane to reduce the amplitude of [Ca 2+ ] i transient or promoting Ca 2+ decline by increasing phospholamban phosphorylation [26,34]. Recently, we have shown that nNOS protein expression and activity are up-regulated in left ventricular (LV) myocytes from hypertensive rat hearts whereas endothelial NOS (eNOS) protein expression is reduced [13]. nNOS facilitated myocardial lusitropy by reducing myofilament Ca 2+ sensitivity; myofilament Ca 2+ desensitization, in turn, increased Ca 2+ handling [13,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in protein kinase G activity (28), changes in myofilament composition, namely regarding titin, a giant sarcomeric protein that mediates restoring forces and lengthdependent deactivation during the early phase of diastole (12) and that we have shown to be hypophosphorylated in this experimental model (9), as well as disturbances in calcium kinetics (13) may justify disturbed cross-bridge detachment and relaxation kinetics. Relaxation is dependent on both crossbridge detachment and calcium kinetics, and impaired protein kinase G signaling that has been reported in HFpEF patients (28) may be involved not only in titin hypophosphorylation but also in increased calcium sensitivity of the myofilaments and slow cross-bridge detachment (14). Recently, in old hypertensive dogs with HFpEF decreased troponin I, Myosin binding protein C, and myosin light chain 2 hypophosphorylation along with increased calcium sensitivity were also described and related to altered protein kinase activity (10), further supporting changes in regulatory myofilament proteins as a likely molecular explanation for delayed relaxation in HFpEF.…”
Section: Discussionmentioning
confidence: 97%
“…Left ventricular cardiomyocytes were superfused in 141.4 mmol/L NaCl, 4 mmol/L KCl, 0.33 mmol/L NaH 2 PO4, 1 mmol/L MgCl 2 , 10 mmol/L HEPES, 5.5 mmol/L glucose, 1.8 mmol/L CaCl 2 and 14.5 mmol/L mannitol, pH 7.4, fieldstimulated (20 V, 2 Hz, 6 ms pulse duration) and changes in sarcomere length during contractions after addition of vehicle or various concentrations of CXCR4/ACKR3 ligands (1 nmol/L to 10 μmol/L) measured using a videosarcomere detection system (IonOptix Corp), as described (38,39). Measurements of 60 steady state contractions were averaged for each condition.…”
Section: Measurement Of Sarcomere Lengthmentioning
confidence: 99%